If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(1/3)*y-(7/2) = -7/4 // + -7/4
(1/3)*y-(7/2)-(-7/4) = 0
(1/3)*y-7/2+7/4 = 0
1/3*y-7/4 = 0 // + 7/4
1/3*y = 7/4 // : 1/3
y = 7/4/1/3
y = 21/4
y = 21/4
| 9/12+2/9 | | 52-5x=2 | | 2x+7=-2x+7 | | 9(b-4)-7b=5(3b-10) | | 1/12y=15 | | 8+4b=18 | | 3/7=-4/x+5 | | (-5/c)=(1/3) | | 1/4(20-4x)=6-x | | 12-q=8 | | x+7/3=7 | | (2/7)=(x/-42) | | -4-x=6x-4 | | y-8+6y=-9+5y+1 | | 12=e/12 | | 7x+8=8+6x | | 4x+11=5x+4 | | x+1.35=2 | | -4/7-1/2v=-2/3 | | 3w=4w+-10 | | (7/10)*(4/5) | | 3-4x=2x+21 | | (x/4)=(3/2) | | 44=28-4(x-2) | | 5/14=p/49 | | 5x+10=-100 | | -4x+7=-6x+17 | | E/12=13 | | 20-d=13 | | 15-3y+2=5 | | 4((x^2)-6x+9)=192 | | 8.5-32=-82 |